Identification of a UPC2 Homolog in Saccharomyces cerevisiae and Its Involvement in Aerobic Sterol Uptake - Shianna, Kevin V. (American Society for Microbiology, 2001)
Saccharomyces cerevisiae normally will not take up sterols from the environment under aerobic conditions. A specific mutant, upc2-1, of the predicted transcriptional activator UPC2 (YDR213w) has been recognized as a strain that allows a high level of aerobic sterol uptake. Another predicted transcriptional activator, the YLR228c gene product, is highly homologous to Upc2p. In fact, at the carboxy terminus 130 of the last 139 amino acids are similar between the two proteins. Since these proteins are very similar, the effect of mutations in the YLR228c open reading frame (ORF) was compared with like alterations in UPC2. First, the YLR228c ORF was insertionally inactivated and crossed with various UPC2 constructs. Deletion of YLR228c and UPC2 in combination resulted in nonviability, suggesting that the two proteins have some essential overlapping function. The upc2-1 point mutation responsible for aerobic sterol uptake was duplicated in the homologous carboxy region of the YLR228c ORF using site-directed mutagenesis. This mutation on a high-copy vector resulted in an increase in sterol uptake compared to an isogenic wild-type strain. The combination of both point mutations resulted in the greatest level of aerobic sterol uptake. When the YLR228c point mutation was expressed from a low-copy vector there was little if any effect on sterol uptake. Gas chromatographic analysis of the nonsaponifiable fractions of the various strains showed that the major sterol for all YLR228c and UPC2 combinations was ergosterol, the consensus yeast sterol.